Surface hydrophobicity and acidity effect on alumina catalyst in catalytic methanol dehydration reaction. Issue 12 (8th September 2017) - Osman, Ahmed I; Abu‐Dahrieh, Jehad K; Rooney, David W; Thompson, Jillian; Halawy, Samih A; Mohamed, Mohamed A
Abstract: BACKGROUND: Methanol to dimethyl ether (MTD) is considered one of the main routes for the production of clean bio‐fuel. The effect of copper loading on the catalytic performance of different phases of alumina that formed by calcination at two different temperatures was examined for the dehydration of methanol to dimethyl ether (DME). RESULTS: A range of Cu loadings of (1, 2, 4, 6, 10 and 15% Cu wt/wt) on Al2 O3 calcined at 350 and 550 °C were prepared and characterized by TGA, XRD, BET, NH3 ‐TPD, TEM, H2 ‐TPR, SEM, EDX, XPS and DRIFT‐Pyridine techniques. The prepared catalysts were used in a fixed bed reactor under reaction conditions in which the temperature ranged from 180–300 °C with weight hourly space velocity (WHSV) = 12.1 h ‐1 . It was observed that all catalysts calcined at 550 °C (γ‐Al2 O3 support phase) exhibited higher activity than those calcined at 350 °C (γ‐AlOOH), and this is due to the phase support change. Furthermore, the optimum Cu loading was found to be 6% Cu/γ‐Al2 O3 with this catalyst also showing a high degree of stability under steady state conditions and this is attributed to the enhancement in surface acidity and hydrophobicity. CONCLUSION: The addition of copper to the support improved the catalyst properties and activity. For all the copper modified catalysts, the optimum catalyst with high degree of activity and stability was 6% copper loaded on gamma alumina. © 2017 The Authors. Journal of Chemical Technology & Biotechnology published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.